Dividen, Struktur Kepemilikan dan Tindakan Perataan Laba - Lie, Jesica; Alexander, Nico (Universitas Kristen Krida Wacana, 2023)
Investors' desire towards the company's profit target encourages management to take income smoothing actions making an appearance that profits are stable, but in fact, profits are not as high as stated. Income smoothing can be affected by a number of variables, including dividend payout amounts and the ownership structure of a company. In order to examine the impact of dividend payments and ownership structure on income smoothing activities in non-financial companies, this study was carried out. The sample in this study comprised of 53 non-financial companies chosen using purposive sampling from the population of non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The level of dividend payment had an impact on the income smoothing, according to the results of the logistic regression analysis that was used to test the hypothesis. The more dividends the company pays out, the more likely management will employ earnings smoothing. Companies typically flatten earnings to meet the amounts of dividends to be given to shareholders so that companies can continue to pay dividends to investors. This study informs shareholders on the company's practices for adjusting earnings to accommodate for dividend payments, enabling them to make more prudent portfolio decisions going forward. Keywords: Income smoothing, dividend, ownership structure.